Quantification of in vivo colonic motor patterns in healthy humans before and after a meal revealed by high‐resolution fiber‐optic manometry. Issue 10 (11th August 2014) - Dinning, P. G.; Wiklendt, L.; Maslen, L.; Gibbins, I.; Patton, V.; Arkwright, J. W.; Lubowski, D. Z.; O'Grady, G.; Bampton, P. A.; Brookes, S. J.; Costa, M.
Abstract Background Until recently, investigations of the normal patterns of motility of the healthy human colon have been limited by the resolution of in vivo recording techniques. Methods We have used a new, high‐resolution fiber‐optic manometry system (72 sensors at 1‐cm intervals) to record motor activity from colon in 10 healthy human subjects. Key Results In the fasted colon, on the basis of rate and extent of propagation, four types of propagating motor pattern could be identified: (i) cyclic motor patterns (at 2–6/min); (ii) short single motor patterns; (iii) long single motor patterns; and (iv) occasional retrograde, slow motor patterns. For the most part, the cyclic and short single motor patterns propagated in a retrograde direction. Following a 700 kCal meal, a fifth motor pattern appeared; high‐amplitude propagating sequences (HAPS) and there was large increase in retrograde cyclic motor patterns (5.6 ± 5.4/2 h vs 34.7 + 19.8/2 h; p < 0.001). The duration and amplitude of individual pressure events were significantly correlated. Discriminant and multivariate analysis of duration, gradient, and amplitude of the pressure events that made up propagating motor patterns distinguished clearly two types of pressure events: those belonging to HAPS and those belonging to all other propagating motor patterns. Conclusions & Inferences This work provides the first comprehensive description of colonic motor patterns recorded by high‐resolution manometry and demonstrates an abundance of retrograde propagating motor patterns. The propagating motor patterns appear to be generated by two independent sources, potentially indicating their neurogenic or myogenic origin.